A Novel Strain Hardening Index SHI for Long-Chain Branched Polymer Melts (Annual Transactions of the Nordic Rheology Society, 2025)
Strain hardening of polymer melts in extensional flows is considered as a desirable rheological feature because it stabilizes the homogeneity of free surface flows, such as e.g., film blowing, blow molding, and fiber spinning. Relating strain hardening to molecular characteristics has been a long-standing challenge in rheology, but while long-chain branching (LCB) is known to be a decisive feature to enhance strain hardening, a quantitative relation between strain hardening and molecular topology is still missing. We propose a novel strain hardening index SHI, that can be used to assess the strain hardening behaviour and to compare the strain hardening of polymer melts with different topologies and different chemistries investigated at different temperatures.